Workers' health policies in Brazil: historical contradictions and possibilities for development - Hurtado, Sandra Lorena Beltran; Simonelli, Angela Paula; Mininel, Vivian Aline; Esteves, Thais Vieira [UNESP]; Vilela, Rodolfo Andrade de Gouveia; Nascimento, Adelaide (Abrasco - Brazilian Association Of Collective Health, 2022)
The Workers??? Health (WH) approach understands that it is necessary to expand the ob-ject of public policies to transform the work proces-ses that determine the health-disease relationship. This broadening brings challenges that drive the development of the formulation and implemen-tation of policies for the surveillance and preven-tion of diseases. This article aimed to analyze the development of Brazilian policies on WH from the perspective of historical contradictions. To this end, the analytical concept of contradiction from Cultural-Historical Activity Theory was used. This is a scoping review, including 64 the-oretical and empirical studies and gray literature published between 1991 and 2019. The results of the analysis showed that: from the change of the object of prevention inserted by the WH appro-ach, five new contradictions emerged that are re-lated to the predominance of instruments of the previous activity model, normative and training instruments, division of labor for assistance and surveillance actions, intra and intersectoral arti-culations. and social control. These contradictions have driven some changes, but some limitations persist around a challenging object.
Keywords: Workers:health policy; Workers: heal-th services; Workers: health surveillance